MODEL PEMILIHAN MODA ANGKUTAN UMUM (STUDI KASUS RUTE MEULABOH – BANDA ACEH) - Irfan Irfan; Muhammad Isya; Renni Anggraini (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
The availability of means of public transport provide more options for travelers to choose the most suitable type for them to use. Mini bus is the type of means of public transport which is most often used in Meulaboh for long distance intercity traveling. Recently, there has been also available a new travel mode which applies the relatively expensive tariff system compared with the tariff of minibus. The problem then occurs when such travel mode has been largely chosen by the travelers. The travel permit held by this travel mode is only a transport business license for operation of tourism transport only. The purposes of this study were to investigate the characteristics of the travelers and to obtain a model of the travel model that could explain the probability of the travelers in selecting the type of means of public transport on Meulaboh – Banda Aceh route. To formulate the behavior of travelers in choosing the transport mode, the stated preference techniques in the form of questionnaire was used. The results of the data were analysed by using multiple linear regression to obtain the utility equation which was then substitutedinto the function of the binomial logit. From the results of multiple linear regression analysis showed the equations with variables utility: the tariff rate difference (X1), the traveling time difference (X2), the waiting time difference (X3) which have significantly influenced the respondents in choosing transport mode. By using the average value of the existing condition of each variable X1, X2, X3, it was obtained that the value of choice probability of mini bus mode on Meulaboh – Banda Aceh route was 48%. In order to increase the choice probability of mini buse modes up to 80%, it canbe done by increasing the tariff difference to IDR.50,000,-. It means that the tariff of the mini bus mode should be cheaper IDR. 50,000,- or the rates of the new expensive tariff travel mode become more expensive of IDR. 50,000,-.